Development of Recombinant Lactococcus lactis Displaying Albumin-Binding Domain Variants against Shiga Toxin 1 B Subunit - Zadravec, Petra; Marečková, Lucie; Petroková, Hana; Hodnik, Vesna; Perišić Nanut, Milica; Anderluh, Gregor; Štrukelj, Borut; Malý, Petr; Berlec, Aleš (PLoS One, 2016)
Infections with shiga toxin-producing bacteria, like enterohemorrhagic Escherichia coli and Shigella dysenteriae, represent a serious medical problem. No specific and effective treatment is available for patients with these infections, creating a need for the development of new therapies. Recombinant lactic acid bacterium Lactococcus lactis was engineered to bind Shiga toxin by displaying novel designed albumin binding domains (ABD) against Shiga toxin 1 B subunit (Stx1B) on their surface. Functional recombinant Stx1B was produced in Escherichia coli and used as a target for selection of 17 different ABD variants (named S1B) from the ABD scaffold-derived high-complex combinatorial library in combination with a five-round ribosome display. Two most promising S1Bs (S1B22 and S1B26) were characterized into more details by ELISA, surface plasmon resonance and microscale thermophoresis. Addition of S1Bs changed the subcellular distribution of Stx1B, completely eliminating it from Golgi apparatus most likely by interfering with its retrograde transport. All ABD variants were successfully displayed on the surface of L. lactis by fusing to the Usp45 secretion signal and to the peptidoglycan-binding C terminus of AcmA. Binding of Stx1B by engineered lactococcal cells was confirmed using flow cytometry and whole cell ELISA. Lactic acid bacteria prepared in this study are potentially useful for the removal of Shiga toxin from human intestine.
Keywords: rekombinace genetická; Electrophoresis, Polyacrylamide Gel; transport proteinů; Humans; HeLa buňky; sekvenční homologie aminokyselin; elektroforéza v polyakrylamidovém gelu; povrchová plasmonová rezonance; imobilizované proteiny; Recombination, Genetic; podjednotky proteinů; Sequence Homology, Amino Acid; Protein Transport; ribozomy; Protein Binding; Albumins; albuminy; ELISA; lidé; proteinové domény; metody zobrazení buněčného povrchu; Lactococcus lactis; Recombinant Proteins; Ribosomes; Enzyme-Linked Immunosorbent Assay; rekombinantní proteiny; Cell Surface Display Techniques; Surface Plasmon Resonance; shiga toxin 1; Flow Cytometry; HeLa Cells; Protein Subunits; vazba proteinů; Protein Domains; Immobilized Proteins; průtoková cytometrie; Shiga Toxin 1